Assessing Local Communities’ Roles in Geographical Indication Dispute Resolution: Challenges in Southeast Asia - Tantimin, Tantimin; Supasiripongchai, Noppanun; Budi, Henry Soelistyo; Disemadi, Hari Sutra; Agustini, Shenti (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2025)
Geographical Indications require proper protection with adequate mechanisms, including dispute resolution, particularly in the face of further economic developments. This paper evaluates the adequacy of the Indonesian, Malaysian, and Thai frameworks in ensuring the involvement of relevant local communities in GI dispute resolution, employing a normative legal research method and a comparative approach. Findings of this study highlight that Indonesia, Malaysia, and Thailand each establish formal community recognition in GI registration through explicit statutory provisions. However, the translation of this substantive recognition into dispute resolution frameworks reveals procedural gaps. Each country recognizes community involvement yet lacks complete procedural safeguards, with Indonesia providing no institutional representation guidance, Malaysia omitting ADR mechanisms, and Thailand leaving post-registration standing undefined, further heightening the urgency of legal reforms to ensure that local communities in GI disputes and ensuring that they can be involved in many processes that are relevant to the GIs that represent their geographical area and cultural heritage, through formal litigation or ADR.